Tinjauan Yuridis Tindak Pidana Pemalsuan Surat Keterangan Sahnya Hasil Hutan Kayu (Studi Putusan No. 58/Pid.B/2022/Pn.Sdr) - Esa, Ambo (Alauddin Law Development Journal (ALDEV), 2023)
The aim of the research is to find out the application of material law to decisions no. 58/Pid.B/2022/PN.Sdr and to find out what the judges' considerations are in making a decision against the perpetrators of the crime of forging letters. This type of research is normative. The results of this study indicate that: (1) In the application of Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction in its decision, the public prosecutor used a combination of charges, and this practice is appropriated with the existing regulations; (2) Based on the judge's consideration referring to Article 88 paragraph (1) letter "b" of Article 14 of the Prevention and Eradication of Forest Destruction rule, indirectly, the judge's legal considerations for the first indictment are not appropriate where there are differences in the considerations and indictments submitted by the public prosecutor.